The characterization of copper oxide (CuO) with different molar concentration using sol-gel spin-coating method / Nur Izzati Nasir - Nasir, Nur Izzati (2015)
In this research, the Copper oxide (CuO) thin films were deposited on 500um quartz substrates. The CuO thin films widely used in technological field such as sensors, solar cell fabrication, and electrochemical devices. The objectives of this research were to deposit the CuO thin films using spin-coating technique and to study the effects of different molar concentration of the CuO thin films on the structural, thickness, optical and electrical properties. The molar concentration of CuO solutions used were 0.3M, 0.35M, 0.4M, 0.45M and 0.5M that prepared using sol-gel method. These solutions were fom1ed by dissolving copper acetate m isopropanol, diethanolamine and polyethyleneglycol. Then, the solutions were stirred using a hot plate stirrer for ten minutes before deposition process. The CuO solutions with different concentration were formed in the dark blue. The samples were deposited by spinning the quartz substrate on spin coater by dropping the CuO solution. All samples were annealed at 600°C for 1 hour in a furnace. The electrical properties were measured to check their resistivity by two point probe technique. The electrical measurements showed that current increase when the concentration increase. High electrical conductivity of 0.07S/m of CuO thin films were performed at molar concentration of 0.5M. The high concentration can conduct more electricity in the electronic devices. The minimum resistivity about 12.760..m has been obtained at molar concentration of 0.5M. The thicknesses were performed using the surface profiler while the sUifaces morphology were characterized using Field Emission Scanning Electron Microscopy (FESEM). The films surfaces were smooth and uniformly distributed grains. The optical transmittances were measured using UV-Vis spectrometer and they decrease as their concentration increase. The optical band gap of the CuO thin films were measured to be between 1.51 e V and l.9e V. The molar concentration of thin film should be taken into consideration in order to get the best thin films for the device.